Control System (CS) and Data Acquisition (DAQ) architecture for the radiation background monitoring of a Personnel Safety System in the ATLAS cavern - Adamidi, E.; Gazis, E.; Nikita, K. (HNPS Advances in Nuclear Physics, 2019)
EDUSAFE is a 4-year Marie Curie ITN project, which focuses on research into the use of Virtual Reality (VR) and Augmented Reality (AR) during planned and emergency maintenance in extreme environments of high radiation background (HEP experiments, nuclear installations, space, deep sea, etc.) The scientific objective of this project is research into advanced VR and AR technologies for a personnel safety system platform, including features, methods and tools. Current technology is not efficient because of significant time-lag in communication and data transmission, missing multi-input interfaces, and simultaneous supervision of multiple workers who are working in the extreme high radiation background environment. The aim is to technically advance and combine several technologies and integrate them as integral part of a personnel safety system to improve safety, maintain availability, reduce errors and decrease the time needed for scheduled or sudden interventions. The research challenges lie in the development of real-time (time-lags less than human interaction speed) data-transmission, instantaneous analysis of data coming from different inputs (vision, sound, touch, buttons), interaction with multiple on-site users, complex interfaces, portability and wearability. The result is an integrated wearable VR/AR system and Control System which can be implemented and tested as a prototype. The LHC at CERN and its existing Personnel Safety System, requirements and protocols will be used as a test and demonstration platform. In this article the progress of the project will be presented and especially the major contribution of the NTUA team in developing and optimizing the Control System (CS) and the Data Acquisition System (DAQ).